Effect of thermomechanical working on the strengthening of some austenitic steel grades (2009)
"This work studied the effects of degrees of warm-split rolling at different temperatures on the strengths of three different grades of austenitic steels (chrome–manganese, chrome–manganese with Ni and Mo additions, chrome–nickel with Mn and Mo additions). The results were compared with cold-rolling effects on the steel grades. The tensile, hardness and impact strengths of the rolled products were obtained. The results showed that thermomechanical working remarkably influenced the properties of the alloys. The trend in property change was dictated by both the degree and temperature of deformation. It was concluded that warm deformation at 350 _C and degree of deformation between 20% and 30% enhanced the plasticity values (toughness and ductility) of the alloys. "